Numerical simulations of a line plume impinging on a ceiling in cold fresh water. (May 2017) - George, Alabodite M.; Kay, Anthony
Highlights: A computational model is used to study warm, buoyant plumes in cold water in a shallow cavity. Buoyancy reversal occurs after the plumes impinge on the ceiling. Mixed water sinks back to the floor and spreads as a dense gravity current. A light gravity current may spread along the ceiling if the source temperature is sufficiently high. Abstract: Laminar plumes from a line source of warm water at the base of a shallow, homogeneous body of cold water (below the temperature of maximum density) were simulated by a computational model. The plume water undergoes buoyancy reversal as it mixes with the cold ambient. If this occurs before the plume has reached the ceiling of the domain, the plume flaps from side to side. Otherwise, it spreads along the ceiling and then sinks, with a vortex enclosed between the rising plume and the sinking flow. Some of the dense, mixed water from the sinking flow is re-entrained into the rising plume, while the rest flows outwards along the floor. However, with high source temperatures, a sufficient volume of warm water eventually builds up to also form a positively buoyant gravity current along the ceiling.